PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PNM MEKAAR, STUDI KASUS KARYAWAN LEVEL ACCOUNT OFFICER DI PNM MEKAAR KOTA BOGOR TAHUN 2021 - Prihatina Jati; Zaharuddin Zaharuddin; Ahmad Firdaus; Merphino Soelaksmono (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2022)
The objectives of this research are: 1) To find out and get a study about the influence of work leadership on employee performance. 2) To find out and get a study about the effect of motivation development on employee performance. 3) To find out and get a study about the influence of competence on employee performance. 4) To find out and get a study about the influence of leadership, motivation and competence simultaneously on PNM Mekaar employees at Account Officer level in Bogor City.The results of this study indicate that: 1) There is an influence of leadership (X1) on employee performance (Y), as evidenced by the tcount value for the X1 variable (Leadership) of 5,225, while the ttable value for n = 80 is 1,990. So 5.225 1.990, it can be concluded that partially Leadership (X1) has an effect on Employee Performance (Y). 2) There is Motivation (X2) on Employee Performance (Y), it is proven that the tcount value for the X2 variable (Motivation) is 7388, while the ttable for n = 80 is 1,990. So 7.388 1.990, it can be concluded that partially motivation (X2) has an effect on employee performance (Y). 3) There is Competence (X3) on Employee Performance (Y), it is proven that the tcount value for the X2 variable (Motivation) is 7,388, while the ttable value for n = 80 is 1,990. So 7.388 1.990, it can be concluded that partially Motivation (X2) affects Employee Performance (Y).) There is an influence of Leadership (X1), Motivation (X2) and Competence (X3) together on Employee Performance (Y). It is evident from the ANOVA test that the Fcount value is 48.927, while the Ftable ( 0.05) for n = 80 is 2.49. So Fcount from Ftable ( 0.05) or 48.927 2.49 with a significant level of 0.000 because 0.000 0.05, it can be said that Leadership (X1), Motivation (X2) and Competence (X3) together or simultaneously have a positive effect on Employee Performance (Y). Based on the calculations in the table above, the effect of the three variables was tested, and based on the Model Summary table, the R Square value was 0.659. This shows that 65.9% Leadership (X1), Motivation (X2), Competence (X3) on Employee Performance (Y) while the remaining 34.1% is influenced by other factors not examined in this study.Keywords: Work Motivation, Career Development, Competence, Employee Performance